Sintesis dan Karakterisasi Senyawa Turunan 2-Benzamido- N-Benzoilbenzamida - Ani Riani Hasana; Siswandono Siswandono; Marcellino Rudyanto (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
Anthranilamide derivatives exhibit anti-inflammatory, antipyretic, antibacterial, antiangiogenic, and anticoagulant properties. With an early in silico examination of its analgesic capabilities, this study aimed to generate a novel anthranilamide molecule by altering 2-Benzamido-N-Benzylbenzamide. Modification of anthranilamide with 1/2/3-chloro benzoyl chloride by acylation resulted in the design, synthesis, characterization, and research of the analgesic effects of 2-benzamido-N-benzoylbenzamide derivatives. 2-(2-chlorobenzamido)-N-(2-chlorobenzoyl)benzamide, 2-(3-chlorobenzamido)-N-(3-chlorobenzoyl)benzamide, and 2-(4-chlorobenzamido)-N-(4-chlorobenzoyl)benzamide were prepared. The nucleophilic acyl substitution reaction method was used to prepare these three chemicals by interaction with anthranylamide and benzoyl chloride molecules. Melting point and thin-layer chromatography were used to check the purity of the synthesis fi ndings. The structure was confi rmed by UV-Vis and infrared spectrophotometry.